Managing Non-Core Liabilities and Leverage of the Banking System : A Building Block for Macroprudential Policy Making in Korea - Alichi, Ali (IMF Working Papers; Working Paper ;, 2012)
Korea has been active in implementing targeted macroprudential policies to address specific financial stability concerns. In this paper, we develop a conceptual model that could serve as a building block for the broader framework of macroprudential policy making in Korea. It is assumed that the policy maker imposes taxes on key aggregate financial ratios in the banking system to mitigate excessive leverage over the economic cycle. The model is calibrated for Korea. The results illustrate how countercyclical tools, such as simple taxes on key financial ratios, could be incorporated to enrich the broader macroprudential policy framework in the Korean context.